Conservation and the social sciences: Beyond critique and co‐optation. A case study from orangutan conservation. Issue 1 (20th January 2020) - Chua, Liana; Harrison, Mark E.; Fair, Hannah; Milne, Sol; Palmer, Alexandra; Rubis, June; Thung, Paul; Wich, Serge; Büscher, Bram; Cheyne, Susan M.; Puri, Rajindra K.; Schreer, Viola; et al.
Abstract: Interactions between conservation and the social sciences are frequently characterized by either critique (of conservation by social scientists) or co‐optation (of social scientific methods and insights by conservationists). This article seeks to push beyond these two dominant positions by exploring how conservationists and social scientists can engage in mutually transformative dialogue. Jointly authored by conservation scientists and social scientists, it uses the global nexus of orangutan conservation as a lens onto current challenges and possibilities facing the conservation–social science relationship. We begin with a cross‐disciplinary overview of recent developments in orangutan conservation—particularly those concerned with its social, political and other human dimensions. The article then undertakes a synthetic analysis of key challenges in orangutan conservation—working across difference, juggling scales and contexts and dealing with politics and political economy—and links them to analogous concerns in the conservation–social science relationship. Finally, we identify some ways by which orangutan conservation specifically, and the conservation–social science relationship more generally, can move forward: through careful use of proxies as bridging devices, through the creation of new, shared spaces, and through a willingness to destabilize and overhaul status quos. This demands an open‐ended, unavoidably political commitment to critical reflexivity and self‐transformation on the part of both conservationists and social scientists. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstrak: Interaksi antara konservasi alam dan ilmu sosial sering dikarakteristikan dengan kritik (konservasi oleh ilmuwan sosial) atau kooptasi (metode ilmu sosial oleh praktisi konservasi). Artikel ini berupaya untuk melampaui dua posisi dominan ini, dengan menggali bagaimana praktisi konservasi dan ilmuwan sosial bisa berdialog secara transformative untuk kedua pihak. Artikel ini ditulis secara bersama oleh ilmuwan konservasi dan ilmuwan sosial, dan menggunakan perhubungan (nexus) global konservasi orangutan sebagai lensa untuk melihat tantangan dan peluang yang saat ini dihadapi oleh hubungan antara konservasi dan ilmu sosial. Kami mulai dengan tinjauan lintas keilmuan mengenai perkembangan terkini dalam konservasi orangutan—khususnya yang berkaitan dengan dimensi sosial, politis, dan dimensi manusia lainnya. Artikel ini kemudian melakukan analisis sintesis dari tantangan‐tantangan utama dalam konservasi orangutan—bekerja menjembatani perbedaan, menggabungkan berbagai skala dan konteks, dan menangani masalah politik dan ekonomi politik—yang dihubungkan dengan keprihatinan terkait dalam hubungan antara konservasi dan ilmu sosial. Pada akhirnya, kami mengidentifikasi beberapa cara bagaimana konservasi orangutan secara khusus, dan hubungan konservasi dan ilmu sosial secara umum, dapat diperbaiki: penggunaan proksi/perwakilan secara cermat sebagai alat penghubung, penciptaan ruang bersama yang baru, dan kebersediaan untuk merombak status quo. Upaya ini membutuhkan komitmen yang terbuka dan yang tidak terhindarkan dari politik untuk refleksi kritis dan transformasi diri, dari kedua belah pihak konservasi dan ilmuwan sosial.